DYNAMICS OF PAIN AND DISABILITY AFTER SURGICAL TREATMENT OF SUPRASPINATUS TENDON INJURIES AND A PROGRESSIVE PHYSICAL THERAPY PROGRAM - Veremii, А. О.; Lazarіeva, О. B.; Kletskova, O. М. (Rehabilitation and Recreation, 2025)
Introduction. Prolonged immobilization after surgical treatment of supraspinatus tendon injuries causes negative biochemical and morphological changes in connective tissue. The aim of the work is to compare the effectiveness of progressive and classical physical therapy programs after surgical treatment of supraspinatus tendon injuries in terms of pain and disability. Materials and methods. The study included 63 patients undergoing surgical treatment and rehabilitation. The Shoulder Pain and Disability Index (SPA-DI) was assessed before surgery, 3 and 6 months after surgery. Patients in the main group (МG) underwent a progressive physical therapy program, and those in the control group (CG) underwent a classical program. The physical therapy programs differed in the duration of immobilization. In the CG, immobilization of the shoulder joint lasted from 4 to 6 weeks in a Dezo bandage or using an abduction bandage. The kinesiotherapy program began after this period. In МG patients, immobilization also lasted up to 6 weeks, but an abduction bandage was used during the first week of strict immobilization. In the future, protection of the shoulder joint was provided with a bandana bandage or sling. From the second postoperative week, patients removed the fixation sling to perform a progressive kinesiotherapy program under the supervision of a physical therapist. Results. In the CG, the SPADI value decreased from 73.08 ± 7.47 points to 39.88 ± 3.12 after 3 months and to 10.10 ± 0.49 points after 6 months. Among МG patients, a consistent decrease in SPADI was observed from 62.47 ± 19.30 points to 39.46 ± 13.36 after 3 months and 9.83 ± 2.67 points after 6 months. At the beginning of the study, the SPADI index values were significantly higher in the CG compared to the МG, which indicates a worse initial functional state in МG patients (p = 0.003). 3 months after surgery measures, no statistically significant intergroup differences were found (p = 0.87). After 6 months, OG values were significantly lower than in the CG (p < 0.001). In both groups, the dynamics were significant. Conclusions. The high effectiveness of progressive and classical physical therapy programs was confirmed. Among patients in the МG and CG, a statistically significant improvement in the SPADI index was noted. Initial indicators were worse in the СG. After 3 months, the results were the same in the groups. After 6 months, the MG had statistically better results, which indicates the advantages of the progressive physical therapy program.